(untitled) - Otey, Michael (Berkeley, California, 1999)
SQL server 7 developer's guide combines start-to-finish coverage of core SQL server 7 concepts with step-by-step programming examples in text and on CD-ROM. It also provides special tutorials on relational database concepts and building SQL statements - plus a complete guide to using Visual Basic for SQL server application development
Keywords: SQL (computer program language),Computer programming (electronic computers),Database administration,SQL (ngôn ngữ lập trình máy tính),Chương trình máy tính (máy tính điện tử),Quản trị dữ liệu